2015
DOI: 10.3109/14767058.2015.1098614
|View full text |Cite
|
Sign up to set email alerts
|

Gastric fluid versus amniotic fluid analysis for the identification of intra-amniotic infection due toUreaplasmaspecies

Abstract: Objective Early neonatal sepsis is often due to intra-amniotic infection. The stomach of the neonate contains fluid swallowed before and during delivery. The presence of bacteria as well as neutrophils detected by culture or Gram stain in the gastric fluid during the first day of life is suggestive of exposure to bacteria or inflammation. We undertook this study to determine the relationship between gastric fluid analysis and amniotic fluid obtained by transabdominal amniocentesis in the detection of Ureaplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 205 publications
(107 reference statements)
2
8
1
Order By: Relevance
“…The observation from paired samples used in a recent study showed a lower rate of Ureaplasma species in gastric fluid samples at the time of delivery than in amniotic fluid samples at the time of admission. 27 This conflicts with the results in our study. We found a higher rate of Ureaplasma species in gastric fluid than in amniotic fluid.…”
Section: Demographic and Clinical Characteristics Of The Study Populacontrasting
confidence: 99%
See 1 more Smart Citation
“…The observation from paired samples used in a recent study showed a lower rate of Ureaplasma species in gastric fluid samples at the time of delivery than in amniotic fluid samples at the time of admission. 27 This conflicts with the results in our study. We found a higher rate of Ureaplasma species in gastric fluid than in amniotic fluid.…”
Section: Demographic and Clinical Characteristics Of The Study Populacontrasting
confidence: 99%
“…25,26 Ureaplasma species are also the most common bacteria in gastric fluid. 27 Similar to previous observations in amniotic fluid and maternal or umbilical cord blood, the intensity of inflammatory response in gastric fluid to Ureaplasma species was dose-dependent. [28][29][30][31] This suggests that bedside IL-6 assessment of gastric fluid samples positive for Ureaplasma species might be useful in predicting the microbial burden.…”
Section: Demographic and Clinical Characteristics Of The Study Populasupporting
confidence: 87%
“…There was no significant difference if both amniotic fluid and gastric fluid were tested positive 22) .…”
Section: Ureaplasma and Diagnosismentioning
confidence: 97%
“…Recently, a study analyzed gastric fluid versus amniotic fluid of preterm infants for the identification of intra uterine infec tions 22) .…”
Section: Ureaplasma and Diagnosismentioning
confidence: 99%
“…In previous studies using culture based techniques, gastric fluid collected immediately after birth identified Ureaplasma species was also present in amniotic fluid, with high specificity but low sensitivity 12 In addition, cytokines present in gastric fluid aspirated immediately after delivery have been associated with chorioamnionitis (indicating placental inflammation) and funisitis (indicating fetal inflammation). 13 In this pilot study, we present for the first time fluid samples from gastric aspirate collected within an hour of birth from both term and pre-term infants for analysis of microbes.…”
Section: Introductionmentioning
confidence: 95%